Exploring critical factors for tourist satisfaction : an empirical investigation on Malaysia as an Islamic tourist destination - Khan, Abdul Highe (International Islamic University Malaysia, 2013)
This research is intent to identify the factors that are influencing tourist satisfaction in Islamic tourist destination in Malaysia. Data were collected through distributing self-structured questionnaire among the Muslim tourists in significant Islamic tourist destinations in Malaysia. This research proposed a conceptual framework to examine the relationship among religious motivation, destination selection, destination image, perceived value, service quality on tourist satisfaction. Factor Analysis was used to test the factorial validity of constructs and Structural Equation Modeling (SEM) was used to test the goodness of the proposed hypothesized model. The empirical results of this research provide justifiable evidence that the proposed conceptual framework of tourist satisfaction is acceptable. The findings of this research indicated that Malaysian Islamic destination has acceptance to the Muslim tourists all around the world. The results depict that religious motivation, destination image, service quality are the important antecedents to tourist satisfaction in Islamic tourist destination. Interestingly the result shows that perceived value is negatively related with tourist satisfaction. In addition religious motivation is not significantly related with destination selection as well as destination selection is not significantly related with destination image. The findings of this research are valuable asset for travel and tour business companies and tourism Malaysia. Academician, researchers, tourism policy makers can also benefit from this research and its findings.